Qualitative Analysis of Rhodamine B Dye on Usek Crackers Sold by Producers in Kasepuhan Village, Batang District - Agustin, Dewanti Queen; Khasanah, Kharismatul (Advances In Social Humanities Research, 2024)
This study aimed to evaluate the presence of Rhodamine B dye in usek crackers produced by local manufacturers in Kasepuhan Village, Batang District, Batang Regency. The use of Rhodamine B in food products poses a serious health risk to the community, as it is a banned dye due to its negative impact on human health. The study used the Wool and Thin Layer Chromatography (KLT) method to identify the presence of Rhodamine B in the samples. The results showed that 12 of the 13 samples tested were positive for Rhodamine B, indicating that food manufacturers still use Rhodamine B dye in their products. This discovery highlights the importance of regular monitoring and evaluation to ensure the safety and quality of food products. The study's findings can be used to inform the public about the risks of consuming Rhodamine B-containing food products and to encourage the use of natural dyes in food production.